Circular Economy in the Agricultural Sector - Anak Agung Sagung Devi Suamba Pradnyandari; Gede Mekse Korri Arisena (Faculty of Agriculture Udayana University, 2026)
BACKGROUND AND OBJECTIVES The circular economy has become a key issue in recent years, seen as capable of addressing economic and environmental challenges while simultaneously fostering the creation of a sustainable ecosystem. The Indonesian government has begun adopting this concept in its 2020 - 2024 development plan, with the agricultural sector as one of the areas with significant potential for its application. This study aims to describe the circular economy concept and its relevance to agriculture, identify the potential and challenges of its implementation in Indonesia, and formulate strategic recommendations. METHODSA literature review of academic sources and policy documents to gain a comprehensive understanding of the circular economy implementation model and approach in the agricultural sector. FINDINGSThis study reveals that implementing a circular economy in the agricultural sector has significant potential to increase resource efficiency, reduce waste, and improve environmental sustainability. However, various challenges remain, including limited access to financing, inadequate infrastructure, weak agricultural extension services, and insufficient business support. Comparisons with international practices, such as China's zero-waste city initiative and Europe's integrated food model, demonstrate that regulatory frameworks, technological innovation, and stakeholder collaboration are key drivers of circular economy adoption in agriculture. CONCLUSIONBased on these findings, the successful implementation of a circular economy in agriculture requires strengthened regulations, financial and technological support, and cross -sector collaboration, as demonstrated by international practice. With these steps, the agricultural sector can transform into a more resilient, sustainable system capable of maintaining ecological balance and food security.